Persepsi Mahasiswa UINSU Terhadap Perbankan Syariah - Naila Umniati; Cindy Sintya; Chairina Chairina (CV. Ulil Albab Corp, 2023)
The unrest among Islamic scholars about the development of finance in Indonesia, which is increasingly deviating from Islamic law, has prompted them to agree to establish an Islamic financial institution. Until now the growth of Islamic banks is still far behind that of conventional banks. But more and more Islamic banking continues to make rapid progress which is marked by the increasing number of Islamic monetary institutes that have been established. The first sharia banking established in Indonesia, namely PT Bank Muamalat Indonesia (BMI), whose development letter was signed on November 1, 1991. Until now, conventional banks have also opened several sharia bank units at their founding, such as BRI Syariah and BNI Syariah.